Diagnostic Radionuclides Labeled on Biomimetic Nanoparticles for Enhanced Follow‐Up Photothermal Therapy of Cancer. Issue 20 (14th July 2021) - Yi, Xuan; Shen, Mengling; Liu, Xinpei; Gu, Jingyu; Jiang, Zewei; Xu, Lixing; Yang, Kai
Abstract: Imaging‐guided local therapy is the most effective strategy to treat primary cancers in patients. However, the local therapeutic effect should be further improved under the premise of absence of induction of additional side effects. It would be meaningful to analyze the potential assistance of nuclear imaging to the follow‐up treatments. In this study, cancer‐targeted copper sulfide nanoparticles with 99m Tc labeling ( 99m Tc‐M‐CuS‐PEG) are prepared using‐cancer cell membranes as a synthesis reactor and applied for the potential single‐photon emission computed tomography/photoacoustic imaging‐guided and 99m Tc‐amplified photothermal therapy of cancer. Owing to the homologous targeting capability of the cancer cell membrane, M‐CuS‐PEG selectively accumulates in homologous tumor sites. After labeling with 99m Tc, M‐CuS‐PEG with a high near‐infrared light absorbance can realize bimodal imaging‐guided photothermal therapy of cancer. Furthermore, the labeled 99m Tc significantly enhances the cell uptake of M‐CuS‐PEG by inducing G2/M arrest of the cell cycle, further improving the photothermal antitumor effect, which is positively correlated with endocytosis of the photothermal conversion reagent. Therefore, a novel cancer‐targeted theranostic nanoplatform is developed and it is revealed that the labeled 99m Tc can not only guide but also amplify the subsequent therapy of cancer, providing a conceptual strategy for cancer theranostics with a high biosafety. Abstract : In this study, homologous tumor‐targeted copper sulfide nanoparticles are prepared using a tumor cell membrane as the template. After labeling with 99m Tc, these nanoparticles realize a perfect imaging‐guided photothermal therapy of cancer. Furthermore, the labeled 99m Tc improves the follow‐up therapeutic efficiency by enhancing the cellular uptake of nanoparticles both in vitro and in vivo.